Kepastian Hukum Kreditur Preferen Dalam Upaya Parate Executie Perjanjian Fidusia Menurut Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia - Setiawan, Rizky Andaru; Ismono, Joko (Law and Humanity, 2023)
Fidusia comes from the word fides means belief. Juridically, the Fiduciary Giver has transferred his material rights to the Fiduciary Giver gives the Fiduciary Giver the right to control the fiduciary guarantee object. Based on UUJF, it has been regulated to the execution of the Fiduciary Guarantee Object if the giver of fiduciary fails to promise by the execution of the executorial title. Through the decision of the Constitutional Court Number 18/PUU-XVII/2019 that in order to carry out an execution if the debetor does not wish to voluntarily submit the Fidicuary Guarantee Object, it must be requested to the Chair of the Court and the determination of breach of contract must have an agreement between creditors and debtors or through legal remedies. Then questioned the legal certainty of preferred creditors in the efforts of the parate executie. This legal research is a normative legal research. The analytical method for this type of normative legal research is a prescriptive method using a statute approach and a case approach. This study aims to determine the legal certainty of preferred creditors in the efforts of parate executie of the fiduciary agreement based on UUJF and the legal consquences and judges’ considerations which are the basis for deciding the case application for the Constitutional Court Decision Number 18/PUU-XVII/2019. The result of the research conclude that legal certainty legal certainty has been stated in UUJF for creditors by executing Fidicuary Guarantee if the debtor fails the promise. The certainty is included in order to “Demi Keadilan Berdasarkan Ketuhanan Yang Maha Esa” means it has the same executorial power as court decision has obtained permanent legal force. However, in reality the execution process cannot be carried out automatically. so that the execution process becomes longer and it is quite difficult to achieve the executive parate. The Constitutional Court emphasizes on an agreement on when the breach of contract between creditors and debtors occurs so that creditors can carry out the parate executie. So that it is often used by the Fiduciary to take refuge in the interpretation of the Constitutional Court, which is actually the default clause agreed in the agreement.